2023
DOI: 10.21037/jss-22-55
|View full text |Cite
|
Sign up to set email alerts
|

The effect of expandable versus static lordotic interbody implants in minimally invasive spine surgery: patient reported outcomes, sagittal alignment, and restoration of disc height and foraminal height

Abstract: Background Pain and disability due to age-related spinal disorders are increasing due to a more active population placing greater demands on their musculoskeletal system. For patients requiring surgery, spinal fusion is typically indicated. Interbody fusion cages improve fusion rates and restore lordosis, disc height, and foraminal height. Static cages are offered in multiple conformations to account for anatomic variability; however, they have issues related to implant subsidence and loss of lord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Kucharzyk reported lower nonunion rates in the expandable compared to static group (6% vs. 12%) and lower revisions surgery rates (4% vs. 8%) which was statistically insignificant. Even with the variable rates of subsidence previously noted, fusion rates have been reported to be similar between groups ( 13 ). The meta-analysis by Alvi et al found fusion rates to be 75% in expandable and 90% in static (P=0.3) and noted that the type of bone graft affects fusion which was not well documented in many of the studies ( 7 ).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Kucharzyk reported lower nonunion rates in the expandable compared to static group (6% vs. 12%) and lower revisions surgery rates (4% vs. 8%) which was statistically insignificant. Even with the variable rates of subsidence previously noted, fusion rates have been reported to be similar between groups ( 13 ). The meta-analysis by Alvi et al found fusion rates to be 75% in expandable and 90% in static (P=0.3) and noted that the type of bone graft affects fusion which was not well documented in many of the studies ( 7 ).…”
mentioning
confidence: 99%
“…Kucharzyk et al reported that improvement in both ODI and VAS back pain to be significantly more favorable in the expandable cage group at all study visits up to two years and the VAS leg pain to be improved in expandable cage group only at 2 years ( 13 ). Massie et al reviewed 44 patients undergoing MIS TLIF for spondylolisthesis and found correction of segmental angle and sagittal vertical axis at the 90-day visits ( 18 ).…”
mentioning
confidence: 99%
See 3 more Smart Citations